Casting light on energy efficiency: Evidence on consumer inattention and imperfect information - Matthias Rodemeier; Andreas Löschel; Roland Kube (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2017)
We investigate consumer inattention and imperfect information regarding the financial benefits of energy-efficient lighting using a randomized controlled trial with 1,084 observations. Results suggest that subjects generally know about cost savings of LED bulbs - the central lighting technology of the future - but largely underestimate the magnitude of these savings. As a result, stated willingness-to-pay for an LED bulb increases on average by 2.53 exteuro through the provision of information on expected lifetime costs. Consumers also confound technology attributes of energy-efficient alternatives, which further explains low adoption rates of the LED technology.
Keywords: D03; D12; D83; Q41; Q48; 330; Imperfect Information; Inattention; Energy Efficiency Gap; Experimental Economics